Carbonized‐MOF as a Sulfur Host for Aluminum–Sulfur Batteries with Enhanced Capacity and Cycling Life - Guo, Yue; Jin, Hongchang; Qi, Zhikai; Hu, Zhiqiu; Ji, Hengxing; Wan, Li‐Jun (Advanced functional materials, 2019)
The rechargeable aluminum–sulfur (Al–S) battery is a promising next generation electrochemical energy storage system owing to its high theoretical capacity of 1672 mAh g−1 and in combining low‐cost and naturally abundant elements, Al and S. However, to date, its poor reversibility and low lifespan have limited its practical application. In this paper, a composite cathode is reported for Al–S batteries based on S anchored on a carbonized HKUST‐1 matrix (S@HKUST‐1‐C). The S@HKUST‐1‐C composite maintains a reversible capacity of 600 mAh g−1 at the 75th cycle and a reversible capacity of 460 mAh g−1 at the 500th cycle under a current density of 1 A g−1, with a Coulombic efficiency of around 95%. X‐ray diffraction and Auger spectrum results reveal that the Cu in HKUST‐1 forms S–Cu ionic clusters. This serves to facilitate the electrochemical reaction and improve the reversibility of S during charge/discharge. Additionally, Cu increases the electron conductivity at the carbon matrix/S interface to significantly decrease the kinetic barrier for the conversion of sulfur species during battery operation. A composite of sulfur anchored on a carbonized HKUST‐1 matrix is developed to serve as a cathode for Al–S batteries, which maintain a reversible capacity of 460 mAh g−1 at the 500th cycle under the current density of 1 A g−1 with a Coulombic efficiency > 95% owing to the decreased kinetic barrier during the electrochemical conversion of sulfur.